Implementation of ABA (Applied Behaviour Analysis) Therapy for Children with Autism Spectrum Disorders at the Therapy Center in the Yogyakarta Special Area - Murti Muninggar (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2021)
This study aims to determine: (1) To explore what techniques in ABA (applied behavior analysis) therapy given by therapists to children with spectrum disorders at the therapy center of the Special Region of Yogyakarta, (2) To implement the implementation of the ABA (applied behavior analysis) therapy process given by the therapist to spectrum disorder children at the Yogyakarta Special Region therapy center, and (3) To reveal whether or not the ABA (applied behavior analysis) therapy given by the therapist to spectrum disorder children in a therapy center for the Special Region of Yogyakarta. The research method in this article uses qualitative research methods. This type of research uses descriptive analysis. Data collection techniques in this study using observation, interviews, and documentation. Data analysis techniques use data reduction, data presentation, and conclusion. Sources of data in this study using primary data and secondary data. The research subjects consisted of therapists, parents, and children with autism spectrum disorders. The results of this study indicate that: (1) ABA (applied behavior analysis) therapy techniques given by therapists to children with spectrum disorders include: instructions, prompts, and rewards, (2) The implementation of ABA (applied behavior analysis) therapy by the therapist is quite good because in this therapy center there is already an adequate program to support the success of children in their development, (3) ABA (applied behavior analysis) therapy given by therapists to children with autism spectrum disorders is very effective because from this therapy the therapists teach children to follow instructions, respond to the words of others, and imitate.